EFEKTIVITAS TERAPI BACAAN AL-QUR’AN BERBASIS DIGITAL TERHADAP PENURUNAN STRES MAHASISWA - Maelina Putri Maratu Solihah; Syafi’in Mansur; Muhamad Zaky Hamdie; Wita Wita; Nikhlah Ziyadaturrohmah (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
Stress is a prevalent mental health issue among university students, intensified by academic pressures and digital-era challenges. This study aims to examines the effectiveness of Surat Ar-Rahman recitation therapy in reducing stress levels among Muslim students at UIN Banten. Using a quasi-experimental design with pre-test and post-test in one group, 25 purposively sampled students participated by completing digital questionnaires via Google Form before and after listening to the Surat Ar-Rahman murotal through an integrated YouTube audio link. Results indicate a significant reduction in stress, with 85% of respondents reporting increased calmness and relaxation post-therapy. The repeated verse,